Numerical Simulation of Magnetohydrodynamic Forced Convective Boundary Layer Flow past a Stretching/Shrinking Sheet Prescribed with Variable Heat Flux in the Presence of Heat Source and Constant Suction - S. P. Anjali Devi; J. Wilfred Samuel Raj (Journal of Applied Fluid Mechanics, 2014)
A study has been carried out on MHD boundary layer forced convection flow along a shrinking surface with variable heat flux in the presence of heat source. The flow is generated due to linear shrinking of the sheet and is influenced by uniform transverse magnetic field. The basic boundary layer momentum and heat transfer equations, which are nonlinear partial differential equations, are converted into nonlinear ordinary differential equations by means of similarity transformation. Numerical solution of the resulting boundary value problem is obtained using Nachtsheim Swigert shooting iteration scheme for the satisfaction of asymptotic boundary conditions along with the Fourth Order Runge Kutta method. The effects of suction parameter, magnetic parameter, Prandtl number, heat source parameter, stretching/shrinking parameter and heat flux parameter on velocity and temperature are shown in several plots. The results are in good agreement with the earlier published works under some limiting cases. Skin friction coefficient and wall temperature are also explored for typical values of the parameter involved in the study.